Obinutuzumab (GA-101), ibrutinib, and venetoclax (GIVe) frontline treatment for high-risk chronic lymphocytic leukemia - Huber, Henriette; Edenhofer, Simone; von Tresckow, Julia; Robrecht, Sandra; Zhang, Can; Tausch, Eugen; Schneider, Christof; Bloehdorn, Johannes; Fürstenau, Moritz; Dreger, Peter; Ritgen, Matthias; Illmer, Thomas; et al. (Blood, 2022)
Despite considerable treatment advances with targeted therapies for patients with chronic lymphocytic leukemia (CLL) deemed high-risk [del(17p) and/or TP53 mutation], the outcome is still inferior compared with other CLL patients. Combining multiple agents with distinct mechanisms of action may further improve outcomes. CLL2-GIVe is an open-label, multicenter trial which enrolled patients with previously untreated CLL with del(17p) and/or TP53 mutation. Patients received induction therapy with obinutuzumab (GA-101), ibrutinib, and venetoclax (GIVe) for cycles 1 through 6 and consolidation therapy with venetoclax and ibrutinib for cycles 7 through 12. Ibrutinib monotherapy was continued for cycles 13 through 36 in patients not reaching a complete response (CR) with serial undetectable minimal residual disease (uMRD) after consolidation. The primary endpoint was CR rate at cycle 15 (final restaging). Secondary endpoints included MRD, survival, and safety. All 41 patients enrolled between September 2016 and August 2018 received study treatment and were included in efficacy and safety populations. With a CR rate of 58.5% at cycle 15, the primary endpoint was met (95% CI: 42.1-73.7; P < .001). At final restaging, 78.0% of patients had uMRD in peripheral blood (PB); 65.9% of patients had uMRD in bone marrow (BM). Estimated progression-free survival (PFS) and overall survival (OS) rates at 24 months were both 95.1%. Adverse events were reported in all patients; most were low grade (grade ≥3: 23.9%). Two deaths were reported (cardiac failure and ovarian carcinoma), neither related to study treatment. The CLL2-GIVe treatment regimen has a manageable safety profile and is a first-line treatment of good efficacy for patients with high-risk CLL.
Prepublished online on blood first edition 15 December 2021
Gesehen am 08.04.2022